STRESS MANAGEMENT FOR TEACHERS: REFLECTION ON SCHOOL’S DAILY ACTIVITIES - Hadi Siswanto (Center of Language and Cultural Studies, 2015)
This paper describes common features of stress for employers and specific problems faced by teachers. The focus of the discussion includes stress definition, various factors cause teacher stress, and the effect of stress for the teacher. After understanding all about stress and indication, it is hoped that teacher will be able to identify and diagnose it. The way how to anticipate and cope with the stress is discussed in this paper.